Analisis Implementasi P5 Di SDN Tanipah 2 Kabupaten Barito Kuala Sebagai Penerapan Kurikulum Merdeka - Nor Aisyah Rosalina; Lili Agustina; Irni Cahyani (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This research is qualitative research with a descriptive approach. The research subjects were principals, students, and class II homeroom teachers at SDN Tanipah 2. Data collection techniques were observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The research results show that the implementation of P5 at SDN Tanipah 2 consists of 3 stages: (1) The planning stage of teachers creating a coordination team, the level of readiness of the educational unit is at the main stage. The teacher chooses the project dimensions, namely the dimension of faith, being devoted to God Almighty and having noble morals and the independent dimension, the theme chosen is the theme of entrepreneurship with time allocated on Tuesdays, and the project topic is my vegetable theme, a manifestation of my responsibility and success. Teachers create project modules; teachers create reporting strategies with monitoring and evaluation instruments. (2) The first implementation stage is the introduction of plants in planting and care. Second, contextual, namely preparing good planting media. The three students' actions involved planting onions and also caring for the plants, preparing to harvest, and packaging the leeks, and using the onions to make omelettes and sell them. (3) In the evaluation activity stage, the teacher makes observations during the activity and uses instruments to monitor program implementation and evaluate the achievement of the Pancasila Student Profile related to dimensions, students compile portfolios and prepare P5 report cards.